2023
DOI: 10.1177/0193841x231189805
|View full text |Cite
|
Sign up to set email alerts
|

From Over-Tourism to Under-Tourism via COVID-19: Lessons for Sustainable Tourism Management

Abstract: With various strains of the novel coronavirus emerging during the last few years, there is a need to reinvent and manage the tourism industry by engaging various stakeholders. Industry and policymakers need to observe the shift and curate tourism-related products and offerings accordingly. In light of the increasing demand for innovations and future directions in the post-COVID-19 period, this article conducts a bibliometric analysis for sustainable tourism studies spanning the years 1990–2021. This paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…In this context, much recent work focuses on the direct and indirect influences of tourism development on residents' quality of life (Hu et al, 2024). In particular, Mahendru et al (2024) highlight the development of research focusing on sustainable tourism to promote local culture and create jobs, in line with the UN development goals .…”
Section: From Sustainability To Inclusiveness: Enhancing Residents' I...mentioning
confidence: 99%
“…In this context, much recent work focuses on the direct and indirect influences of tourism development on residents' quality of life (Hu et al, 2024). In particular, Mahendru et al (2024) highlight the development of research focusing on sustainable tourism to promote local culture and create jobs, in line with the UN development goals .…”
Section: From Sustainability To Inclusiveness: Enhancing Residents' I...mentioning
confidence: 99%
“…The outbreak of COVID-19 has been a major roadblock on the way to implement sustainable development, as it impacted various sectors differently. This scenario has been holistically analyzed by Mahendru et al (2023). The review carried out by the authors have shown the health predicaments brought forth by the COVID-19 outbreak had a severe impact on the tourism and hospitality industry, and the negative impact has been largely experienced in terms of the slump in the job creation in this sector.…”
mentioning
confidence: 99%